Five little pigs - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Hercule Poirot mysteries, 2024)
Beautiful Caroline Crale was convicted of poisoning her husband, yet there were five other suspects: Philip Blake (the stockbroker) who went to market; Meredith Blake (the amateur herbalist) who stayed at home; Elsa Greer (the three-time divorcee) who had roast beef; Cecilia Williams (the devoted governess) who had none; and Angela Warren (the disfigured sister) who cried 'wee wee wee' all the way home. It is sixteen years later, but Hercule Poirot just can't get that nursery rhyme out of his mind...